POTENSI PENANAMAN SIKAP KEMANDIRIAN DAN NILAI RELIGIUS PADA KELUARGA KAMPUNG IDIOT DI PONOROGO - Muslich, Ahmad; Susanto, Happy; Arif, M. Zainal; Ariyanto, Ayok; Rois, Adib Khusnul; Erwahyudin, Devid Dwi; Arifin, Syamsul (MUADDIB Jurnal Kependidikan dan Keislaman, 2021)
Karangpatihan village, Balong sub-district, Ponorogo district is a village that is already known as the ideot village, some of its people have mental retardation (drown syndrome) in the mentally retarded type. Instilling Independence and Religious Values in Idiot's village families in Ponorogo Regency is an effort to relieve idiot families from adversity. In the aspect of independence, the idiot village family tries to produce works or work to fulfill all their needs without having to depend on the welfare of others. In the aspect of inculcating religious values, it is very necessary to help alleviate the problems of idiot families through a spiritual approach that is felt to be very important, with spiritual guidance it is hoped that it can foster faith and piety and provide direction in behavior. The values of worship also play a large role in motivating and guiding a person to do good in the context of social relations with the community.